Recognition of change in the reform of forensic mental health by clinical practitioners: a questionnaire survey in Japan - Shiina, Akihiro (BioMed Central, 2014)
In Japan, new legislation regarding forensic mental health, namely, the Act on Medical Care and Treatment for Persons Who Have Caused Serious Cases under the Condition of Insanity (Medical Treatment and Supervision Act (MTS Act)) was enforced in 2005, although community mental health care remains largely unchanged. We surveyed local clinical psychiatrists by questionnaire to gather information on the influence of the MTS Act on clinical mental health practice. We sent a paper questionnaire to almost all the psychiatrists in the Chiba prefecture, 56% of whom (N = 306) responded. The participants felt that the MTS Act had minimal direct impact on community mental health care. However, some relatively new schemes such as a multiple disciplinary team approach or supervised outpatient care are given more attention than before. These results suggest that this new forensic mental health legislation may assist in the spread of new paradigms into clinical practice.